Alih Fungsi Lahan di Bojong Kondang dalam Perspektif Ekoteologi - Febianitri, Dyanti (Jurnal Riset Agama, 2021)
Excessive land conversion causes negative impacts such as floods, landslides, climate change, and other disasters. This happened in Bojong Kondang, where the slopes of the mountains were used as residential buildings. The purpose of this paper is to describe the main research topics: 1) Community understanding of land conversion in Bojong Kondang; 2) Ecotheological analysis in the perspective of Seyyed Hossein Nasr on land conversion in Bojong Kondang. This research is a field research, with descriptive qualitative method, and the ecotheological theory of Seyyed Hosein Nasr as an analytical tool. The findings in this study are first, there are pros and cons between the community and the government on the housing development. Second, the perpetrators of the housing construction were not native Bojong Kondang residents, but migrants. Third, the indigenous people of Bojong Kondang are very concerned about the environment and uphold ecotheological values based on the principles of Islamic teachings. Fourth, the elders in Bojong Kondang still adhere to mythology.